2012
DOI: 10.1166/asl.2012.3252
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependant Volumetric and Compressibility Studies of Drug-Surfactant Interactions in Dimethylsulfoxide (DMSO) Solutions

Abstract: In this work we present apparent molar volume, v and apparent molar adiabatic compressibility, values of sodium dodecyl sulphate (SDS) in DMSO and in DMSO solution of 0.25 % w/v 6-methyl-4(2-hydroxy-3-methoxyphenyl)-2-thioxo-1,2,3,4-tetrahydro pyrimidine-5 carboxylic acid ethyl ester (a pyrimidine derivative drug). The study was carried out over a temperature range (20-40 C) covering a wide range of SDS concentration (2-11 mmol dm −3. Being highly sensitive to the extrinsic experimental conditions, a differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As in the case of SDS with Gly, Ala, Val and Leu, it was observed that the increasing hydrophobicity from Gly to Leu, the water clathrate-like structure increased with increasing hydrophobicity of these amino acids (Leu > Val > Ala > Gly) resulting into a decrease in CMC of SDS with increasing hydrophobicity of these amino acids [127]. With cationic surfactant, HTAB, similar trends were observed, a decrease in CMC in the sequence Gly-Gly-Gly < Gly-Gly < Gly was seen.…”
Section: Effect Of Amino Acid Ordering On the Assembly Of Surfactantsmentioning
confidence: 90%
“…As in the case of SDS with Gly, Ala, Val and Leu, it was observed that the increasing hydrophobicity from Gly to Leu, the water clathrate-like structure increased with increasing hydrophobicity of these amino acids (Leu > Val > Ala > Gly) resulting into a decrease in CMC of SDS with increasing hydrophobicity of these amino acids [127]. With cationic surfactant, HTAB, similar trends were observed, a decrease in CMC in the sequence Gly-Gly-Gly < Gly-Gly < Gly was seen.…”
Section: Effect Of Amino Acid Ordering On the Assembly Of Surfactantsmentioning
confidence: 90%
“…These parameters are calculated from volumetric and viscometric properties of drugs in solutions 6 . This volumetric and viscometric study of different drugs in different solvent systems have been reported in literature for example, M. Shaikh et al reported viscometric and volumetric properties of paracetamol in ethanol water system at various temperatures, 7 temperature dependent volumetric and compressibility studies of drug‐surfactant interaction in DMSO solution by S. Chauhan et al, 8 apparent molar volumes and B ‐coefficient of sodium salicylate in different solvent systems by A. B. Nikumbh and R. C. Bhujbal 9…”
Section: Introductionmentioning
confidence: 91%
“…Micellization process (formation of micelles) can be studied with the help of different physical properties of solution like conductivity, viscosity, surface tension, etc. [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%